How I Live Now: The Project of Sustainability in Dystopian Young Adult Fiction - Hanssen, Jessica Allen (Studier i Pædagogisk Filosofi, 2018)
It is impossible to ignore the enduring and sweeping popularity of young adult novels (YA) written with a dystopian, or even apocalyptic, outlook. Series such as Th e Hunger Games, Th e Maze Runner, and Divergent present dark and boding worlds of amplifi ed terror and societal collapse, and their vulnerable protagonists must answer constant environmental, social, and political challenges, or risk starvation, injury, and various forms of pain and suff ering. More frequently than not, the tensions of the dystopian YA universe turn to the natural world, one of sustenance and renewal, for resolution. The continued popularity of dystopian fi ction written expressly for young adult readers requires critical examination, as teachers must prepare themselves to deal with the questions raised by these texts. Th e trend toward the dystopian seems like rather a bleak expression of political and social hopelessness, but it does off er certain insights into what young readers want from the world around them. Much of the appeal of the dystopian comes from imagining not just problems, but how to solve them. The ingenuity and resourcefulness displayed in dystopian YA novels is not only appealing, but becomes a bold and ultimately optimistic statement on the need for environmental and social sustainability. The optimal incorporation of dystopian YA into the English as a foreign language (EFL) curriculum relies on the preparation of instruction as understood by Wolfgang Klafki in a mode and format that feels fresh and encourages student-led engagement, genuine multimodality, and an organic progression from the closed circle of the classroom to the open arena of adult civilization.